Peningkatan Hasil Belajar Pengukuran Berat dengan Alat Tidak Baku pada Siswa Kelas 1 SDN 01 Winongo - Setioko, Bagus; Cahyono, Bambang Eko Hari; Andriani, Ike Yusda (FKIP Universitas Wisnuwardhana, 2024)
This study aims to improve mathematics learning outcomes on the topic of weight measurement in grade 1 at SDN 01 Winongo Madiun by utilizing non-standard measuring tools. Initial observations revealed that many students had not met the Minimum Completion Criteria (KKM), indicating that conventional teaching methods were insufficiently effective. This research employs the Classroom Action Research (CAR) method, which includes cycles of planning, implementation, observation, and reflection. In the pre-cycle, only 46% of students met the KKM. The use of non-standard measuring tools in Cycle I increased the percentage of students meeting the KKM to 64%, and adjustments made in Cycle II further improved learning outcomes to 86%. These findings suggest that non-standard measuring tools can enhance students' understanding of weight measurement concepts in a more tangible and interactive manner. The study concludes that this approach is effective in improving mathematics learning outcomes and can serve as a more engaging and applicable teaching method in the classroom.